Analysis of Bobango Traditional Sanctions in Wayaua Village: A Perspective of Restorative Justice and The Concept of Sulh - Rahmat Hi. Abdullah; Pujiyono; Sukirno (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
This study examines the Bobango traditional sanctions practiced in Wayaua Village, South Halmahera, through the lens of restorative justice principles and the Islamic concept of Sulh. Bobango represents a customary conflict resolution mechanism involving deliberation between perpetrators' families, victims' families, and traditional leaders to achieve reconciliation through compensatory fines. Using conceptual and reflective approaches, this research analyzes how Bobango embodies the fundamental characteristics of restorative justice, particularly through its participatory dimension (involving all affected parties in inclusive decision-making) and its restorative dimension (focusing on repairing harm rather than punishing offenders). The findings reveal that Bobango functions as an authentic form of indigenous restorative justice that has been empirically tested for centuries within Indonesian society. Furthermore, from an Islamic legal perspective, Bobango demonstrates perfect harmonization with Sharia principles, operating as a majlis sulh (peace council) where fines serve as badal al-sulh (legitimate compensation) and potentially as ta'zir bi al-mal (financial sanctions for communal benefit). This study concludes that Bobango represents both indigenous and Islamic restorative justice, proving that legal pluralism in Indonesia can function harmoniously when customary law, Islamic law, and national law mutually reinforce each other in realizing substantive justice for a pluralistic society.